Monitoring of r-Hirudin Anticoagulation during Cardiopulmonary Bypass – Assessment of the Whole Blood Ecarin Clotting Time - Pötzsch, Bernd; Madlener, Katharina; Seelig, Christoph; Riess, Christian F; Greinacher, Andreas; Müller-Berghaus, Gert (Thrombosis and Haemostasis, 1997)
The use of recombinant ® hirudin as an anticoagulant in performing extracorporeal circulation systems including cardiopulmonary bypass (CPB) devices requires a specific and easy to handle monitoring system. The usefulness of the celite-induced activated clotting time (ACT) and the activated partial thromboplastin time (APTT) for r-hirudin monitoring has been tested on ex vivo blood samples obtained from eight patients treated with r-hirudin during open heart surgery. The very poor relationship between the prolongation of the ACT and APTT values and the concentration of r-hirudin as measured using a chromogenic factor Ila assay indicates that both assays are not suitable to monitor r-hirudin anticoagulation. As an alternative approach a whole blood clotting assay based on the prothrombin-activating snake venom ecarin has been tested. In vitro experiments using r-hirudin- spiked whole blood samples showed a linear relationship between the concentration of hirudin added and the prolongation of the clotting times up to a concentration of r-hirudin of 4.0 µg/ml. Interassay coefficients (CV) of variation between 2.1% and 5.4% demonstrate the accuracy of the ecarin clotting time (ECT) assay. Differences in the interindividual responsiveness to r-hirudin were analyzed on r-hirudin- spiked blood samples obtained from 50 healthy blood donors. CV- values between 1.8% and 6% measured at r-hirudin concentrations between 0.5 and 4 µg/ml indicate remarkably slight differences in r-hirudin responsiveness. ECT assay results of the ex vivo blood samples linearily correlate (r = 0.79) to the concentration of r-hirudin. Moreover, assay results were not influenced by treatment with aprotinin or heparin. These findings together with the short measuring time with less than 120 seconds warrant the whole blood ECT to be a suitable assay for monitoring of r-hirudin anticoagulation in cardiac surgery.